Peranan Keterampilan Membaca pada Proses Prapenerjemahan dalam Mencapai Kesepadanan Teks Terjemahan - Maya Rahmawati; Sidik Indra Nugraha (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This study examines what strategies are most likely to be used by students when translating as well as the equivalence level of the translated texts. It aims to find out the appropriate reading strategy when translating. This study uses a qualitative paradigm because it seeks to explain a phenomenon about the choice of reading strategies used by students and the equivalence equivalence level of the translated texts. This research produces descriptive data in the form of patterns of reading strategy when students translate two different kinds of texts. In this study, data collection was carried out in two ways, namely questionnaires and translating test. Questionnaire was used to obtain data about the reading strategies chosen by students when translating. The questionnaire used is a closed type in the form of multiple choice. Each item has a different value. From the results of the analysis presented, it can be seen that most students still show a tendency to use bottom-up strategies in the process of translating. In addition, it can be seen that the choice of reading strategy can influence the results of translation. Some translations produced by students who tend to use bottom-up strategies in the translation process are not context-specific and still seem hard to read and unnatural. While around 80% of translations resulting from top-down strategies are considered acceptable because they are in accordance with the rules of the target language and sentence context. In addition, this research can also show that relying solely on one reading strategy can potentially produce erroneous translations.